Immunological properties and protective efficacy of a single mycobacterial antigen displayed on polyhydroxybutyrate beads. Issue 6 (17th July 2017) - Rubio‐Reyes, Patricia; Parlane, Natalie A.; Buddle, Bryce M.; Wedlock, D. Neil; Rehm, Bernd H. A.
Summary: In 2015, there were an estimated 10.4 million new tuberculosis (TB) cases and 1.4 million deaths worldwide. Bacille Calmette–Guérin (BCG), an attenuated strain of Mycobacterium bovis, is the vaccine available against TB, but it is insufficient for global TB control. This study evaluated the immunogenicity of the Mycobacterium tuberculosis antigen Rv1626 in mice while assessing the effect of co‐delivering either Cpe30 (immunostimulatory peptide), CS.T3378–395 (promiscuous T helper epitope) or flagellin (TLR5 agonist) or a combination of all three immunostimulatory agents. Rv1626 and the respective immunostimulatory proteins/peptides were co‐displayed on polyhydroxybutyrate beads assembled inside an engineered endotoxin‐free mutant of Escherichia coli . Mice vaccinated with these beads produced immune responses biased towards Th1‐/Th17‐type responses, but inclusion of Cpe30, CS.T3378–395 and flagellin did not enhance immunogenicity of the Rv1626 protein. This was confirmed in a M. bovis challenge experiment in mice, where Rv1626 beads reduced bacterial cell counts in the lungs by 0.48 log10 compared with the adjuvant alone control group. Co‐delivery of immunostimulatory peptides did not further enhance protective immunity. Abstract : An endotoxin‐free mutant of E. coli (ClearColi) was engineered to assemble polyhydroxybutyrate (PHB) beads which display a vaccine candidate antigen from Mycobacterium tuberculosis . In addition PHB beads were bioengineered to co‐display various immune modulator. Respective beads were injected into mice and the immune response showed that display of a single antigen on PHB beads induces protective immunity independent of co‐displayed immunomodulators.